HUBUNGAN MANUSIA DAN ALAM DALAM QASĪDAT SYAJARAT AZ-ZAYTŪN ATH-THĀNĪYAH KARYA MAHMOUD DARWISH (KAJIAN EKOKRITIK SASTRA LAWRENCE BUELL) - Putri, Amelia Febriana; Nida, Nushrotun; Nugraha, Rahmat Mulya; Nurhidayat, Ari; Pamungkas, Rumi; Al Haqiqi, Muhammad Jundullah (Dirasa Islamiyya: Journal of Islamic Studies, 2025)
This study aims to analyze the relationship between humans and nature in the poem "Qasīdat Syajarat Az-Zaytūn Ath-Thānīyah" by Mahmoud Darwish using Lawrence Buell's ecocritical literary approach. This research employs a qualitative method with descriptive analysis to examine the symbolism and ecological representation in the poem. The results show that the olive tree in Darwish's poem not only serves as an aesthetic symbol but also represents courage, resilience, and adaptive strength in facing environmental challenges. The poem emphasizes the importance of maintaining a harmonious relationship between humans and nature and criticizes destructive actions that harm the environment. The conclusion of this study is that the poem "Qasīdat Syajarat Az-Zaytūn Ath-Thānīyah" can serve as a reflection on contemporary ecological issues and as a medium to raise awareness of the importance of environmental conservation.